Platinum-group element abundances and Re–Os isotopic systematics of the upper continental crust through time: Evidence from glacial diamictites. (15th October 2016) - Chen, Kang; Walker, Richard J.; Rudnick, Roberta L.; Gao, Shan; Gaschnig, Richard M.; Puchtel, Igor S.; Tang, Ming; Hu, Zhao-Chu
Abstract: The fine-grained matrix of glacial diamictites, deposited periodically by continental ice sheets over much of Earth history, provides insights into the average composition and chemical evolution of the upper continental crust (UCC) (Gaschnig et al., 2016, and references therein). The concentrations of platinum-group elements (PGEs, including Os, Ir, Ru, Pt and Pd) and the geochemically related Re, as well as 187 Re/ 188 Os and 187 Os/ 188 Os ratios, are reported here for globally-distributed glacial diamictites that were deposited during the Mesoarchean, Paleoproterozoic, Neoproterozoic and Paleozoic eras. The medians and averages of PGE concentrations of these diamictite composites decrease from the Mesoarchean to the Neoproterozoic, mimicking decreases in the concentrations of first-row transition elements (Sc, V, Cr, Co and Ni). By contrast, Re concentrations are highly variable with no discernable trend, owing to its high solubility. Assuming these diamictites are representative of average UCC through time, the new data are fully consistent with the previous inference that the Archean UCC contained a greater proportion of mafic–ultramafic rocks relative to younger UCC. Linear regressions of PGEs versus Cr and Ni concentrations in all the diamictite composites from the four time periods are used to estimate the following concentrations of the PGEs in the present-day UCC: 0.059 ± 0.016 ng/g Os, 0.036 ± 0.008 ng/g Ir, 0.079 ± 0.026 ng/g Ru, 0.80 ± 0.22 ng/g Pt and 0.80 ± 0.26 ng/g Pd (2 σ of 10, 000 bootstrapping regression results). These PGE estimates are slightly higher than the estimates obtained from loess samples. We suggest this probably results from loess preferentially sampling younger UCC rocks that have lower PGE concentrations, or PGEs being fractionated during loess formation. A Re concentration of 0.25 ± 0.12 ng/g (2 σ ) is obtained from a regression of Re versus Mo. From this, time-integrated 187 Re/ 188 Os and 187 Os/ 188 Os ratios for the UCC are calculated, assuming an average UCC residence duration of ∼2.0 Ga, yielding ratios of 20 ± 12 and 0.80 ± 0.38 (2 σ ), respectively.